Horiba Micros ES 60 Blood Cell Analyzer in Blood Donor Eligibility: A Validation Study - Silvia Tillati; Ilaria Pati; Michela Delle Donne; Alessandra Meneghel; Donatella Londero; Vincenzo De Angelis (Diagnostics, 2022)
Background: Eligibility criteria for blood donation require hemoglobin levels of ≥12.5 g/dL for women and ≥13.5 g/dL for men, and a platelet count of ≥180 × 109/L. Screening methods before donation should ensure high accuracy, precision, and ease in operation. We assessed the performance, precision, and repeatability of the Horiba Micros ES 60 (Horiba) compared to the Beckman Coulter DXH 800. Methods: Performance was compared by testing samples for each of the 11 devices across 6 sites in the Transfusion Service of Friuli Venezia Giulia Region, Italy. We measured precision by calculating the coefficient of variation (CV), concordance with ρ-Pearson’s correlation coefficient, and accuracy with F-tests. The intra-assay agreement was examined in the 11 devices, and repeatability was performed by using CV and the Kruskal–Wallis test. Results: The precision of Horiba was acceptable. Overall, ρ-Pearson’s coefficients indicated a strong correlation and positive relationship between all variables. The Bland–Altman plots showed that most of the differences lay within the limits of agreement. All CV were below the reference threshold for all the parameters. Finally, the Kruskal–Wallis test reported non-significant statistical differences for all parameters, except platelet count (p < 0.000). Conclusions: Horiba is adequate for routine pre-donation screening. The intra-assay agreement further demonstrates the accuracy of the device.